LAKI-LAKI DAN ESTETIKA TUBUH: GYM CULTURE, SKINCARE, DAN CITRA MASKULIN: Kajian Tentang Representasi dan Citra Diri Laki-Laki Dalam Masyarakat Urban Kota Makassar - M. Sayful (Prodi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Filsafat UIN Alauddin Makassar, 2025)
This study aims to understand how men construct their self-image through gym and skincare practices, and how these practices reflect and shape masculine identity within the context of contemporary consumer culture. Using a body anthropology approach, the study draws on Pierre Bourdieu’s concepts of habitus and symbolic capital, as well as Judith Butler’s theory of gender performativity. The male body is examined as both a site of internalized social values and a space for the performative negotiation of masculine identity. Data were collected through in-depth interviews with seven male key informants from various age groups and occupational backgrounds, and analyzed qualitatively and narratively. The findings reveal that Gym practices serve not only for physical fitness but also as a means of cultivating social credibility and an aesthetic form of masculinity. Meanwhile, Skincare is practiced as a site of value negotiation between self-care and adherence to masculine norms. Social media amplifies the visualization of male bodies and creates new pressures for men to appear ‘ideal,’ while at the same time tensions persist between traditional masculinity and emerging lifestyle trends. The study concludes that the male body functions as a complex cultural arena, where value debates, normative shifts, and dynamic gender articulations take place.